PESANTREN TRADITIONS CONTINUED AND TRANSFORMED: Evidence from North Sumatra, Indonesia - Faisal Musa; Saidatul Khairiyah (Journal of Contemporary Islam and Muslim Societies, 2026)
This study examines the continuity and transformation of pesantren traditions through the alumni network of Pesantren Musthafawiyah through a qualitative case study approach. Data were collected through document analysis, interviews, and field observations in several pesantrens established by Musthafawiyah alumni. The data were analyzed using thematic analysis to identify patterns of transmission, reproduction, and adaptation of pesantren traditions within the alumni network. The findings reveal that the alumni network plays a crucial role in sustaining the Musthafawiyah educational traditions. Through the establishment of new pesantrens, alumni reproduce key elements of Musthafawiyah’s educational system, including the study of classical Islamic texts, the authority of the kiai, and the moral formation of santri. At the same time, alumni-founded pesantrens make adaptations, such as the integration of formal schooling systems, curriculum development, and organizational modernization. As such, the continuity of pesantren traditions is embedded in the role of alumni networks as agents of social and educational reproductions. The findings contribute to the broader scholarship on Islamic education by highlighting how pesantren traditions persist and evolve beyond the Javanese context.Keywords: Continuity, transformation, pesantren tradition, alumni network, musthafawiyah, Southern Tapanuli.